(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the main directions of sociolinguistics and their tasks. Synchronous and diachronic, macro and micro sociolinguistics, theoretical and practical sociolinguistics are discussed separately, and a broader understanding of their study objects is given.